Effect of health education-based yoga & naturopathy lifestyle interventions on personality of patients with non-communicable diseases: A randomized controlled trial. Issue 11 (17th March 2023) - Tewani, Gulab Rai; Silwal, Karishma; Yadav, Dinesh; Siddiqui, Aarfa; Kriplani, Sucheta; Maheshwari, Ayush; Nathani, Varsha Vijay; Singh, Deepika; Gyanchandani, Kunal; Iyer, Rukmani; Khan, Vakeel; Dubey, Piyush; et al.
Abstract : Background: Personality traits play a role in the progression and management of chronic diseases. However, a change in personality is seldom considered an outcome in the management of chronic diseases. The present study explored if a health education-based yoga & naturopathy lifestyle intervention group (HYNLG) can induce change in the personality traits, vitality, quality of life (QoL), and satisfaction in patients with non-communicable diseases compared to a therapy-centric yoga & naturopathy lifestyle intervention (TYNLG). Methods: This randomized control trial included 56 participants who were equally randomized into the HYNLG and TYNLG groups. Both groups received a 10-day inpatient regimen that included hydrotherapy, mud therapy, diet therapy, supervised fasting, sunbathing, acupressure, and massage therapy. Additionally, HYNLG received a 10-day orientation (1 h/d) on concepts centered around belief systems, lifestyle changes, and their impact on health. Vedic Personality Inventory, SF-12 QoL questionnaire, visual analog scale, Hamilton Anxiety Inventory, and Visit-Specific Patient Satisfaction Questionnaire were used as outcome measures. The changes between the time points were analyzed using parametric and non-parametric tests, and Pearson correlation was used to investigate the association between the variables. Results: The Sattva (balance and stability) personality trait has significantly increased in HYNLG, while the Rajas (activity and imbalance) and Tamas (inertia and dullness) personalities have decreased. HYNLG also demonstrated a significant improvement in mental QoL, vitality, anxiety reduction, and patient satisfaction when compared to TYNLG. Conclusion: These findings may have serious clinical and public health implications as they provide insights on the usefulness of introducing a health education component into lifestyle modification programs.